Keratoplastyka drążąca w stożku rogówki w 1990 i 1999 roku - Szaflik, Jerzy; Iwaszkiewicz, Ewa; Czubak, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The purpose of this study was to compare grafts performed because of keratoconus in our clinic in years 1990 - 1999. These years were chosen for analysis because in this time some methods of grafting were changed, particularly: material for transplantation, graft's size, method of trephination and graft suturing, also management after operation. The study included 51 patients (17 females, 34 males) with keratoconus, aged 16 to 46 (mean age 31,3), which have had penetrating keratoplasty done in years 1990-1999. The amount of surgery, sex of patients, preoperative preparation, kind of graft material, technique of operation, methods of graft suturing, postoperating procedure, the time of patients hospitalization, time of suture removing, postoperating visual acuity and complication were compared.